Association of Serum Electrolyte Abnormalities in Preterm Low Birth Weight Neonates (Faridpur Medical College Journal, 2020)
Despite decline in under five mortality in the last few decades, neonatal mortality rate has not changed substantially. A large number of these newborn are premature or low birth weight. Premature infants are at increased risk of developing dehydration or overhydration. Therefore, high index of suspicion, prompt recognition and thorough understanding of common electrolyte abnormalities are necessary to improve neonatal outcome. It seems to be essential for immediate management for planning appropriate fluid and electrolyte therapy and thereby for improved outcome. To study the electrolytes abnormalities in preterm low birth weight neonates information were collected who gave consent and participated in the study willingly. Duration of data collection was approximately 6 (Six) months. Patients admitted to the Dhaka Medical College Hospital and after meeting the inclusion and exclusion criteria a simple random sampling technique was applied for selecting the sample patients. Total 50 preterm LBW neonates fulfilling the inclusion criteria were studied during this study period. Abnormal electrolytes were documented in 20(40%) preterm LBW neonates of which hyperkalemia was the predominant electrolyte abnormality found in 8(16.0%) neonates, hyponatremia was found in 7 (14.0%), hypokalemia in 3 (6.0%) and hypernatremia in 2 (4.0%). It was observed that electrolyte abnormalities are common in preterm LBW neonates. So, identification of associated electrolyte abnormalities and proper management of fluid and electrolytes and close monitoring are important.Faridpur Med. Coll. J. Jan 2019;14(1): 31-33